Self Healing Behaviour of Bio Concrete: A Critical Literature Review - Anikait Gupta, Sanjeev Naval (International Journal of Advanced Science and Technology, 2020)
Development of cracks is a common problem found in concrete. This problem is relatively due to low tensile strength. Cracks that occur in concrete are considered to be the major reason for reduced service life of concrete structures. It has been noticed that in moist conditions, the strength of the concrete structures have been decreased and this is due to the entry of chemicals through little pores which results in reduced permeability. To prevent these cracks, it is necessary to treat them at the beginning as it is more advisable otherwise economical crisis happened. Self healing methods are endorsed to overcome these situations. Addition of calcium sources along with urease (an enzyme) generating bacteria results in the precipitation of calcite in concrete. By using bio concrete, strength of concrete structures increases. To use bio concrete on large scale, many researchers are trying their best to overcome the cost of bio concrete.